Zakat sebagai Instrumen Finansial Islami - Tri Hidayati, Nabila; Fauziah , Ana; Sakhariyah Ramadani, Nafakhatus; Desiana Putri, Rani; Firdaus Yudanta, Zulfaa; Nuril Hidayati, Amalia (Teewan Journal Solutions, 2025)
Zakat, as an Islamic financial instrument, plays a crucial role in fostering social and economic justice. This article explores the comparison between zakat and conventional financial instruments to highlight the advantages and uniqueness of zakat. Beyond its religious obligation, zakat serves as a financial tool capable of reducing inequality and promoting fair wealth distribution. Furthermore, the article elaborates on the strategic role of zakat institutions in managing and distributing zakat to eligible recipients, along with innovations in zakat management through the development of more modern and relevant zakat-based products and services. Lastly, it discusses the connection between zakat and the Sustainable Development Goals (SDGs), particularly in areas such as poverty alleviation, improving welfare, and promoting inclusive economic growth. This research method uses a comprehensive and descriptive library research method. Zakat has proven to have significant potential to support the achievement of SDGs through more effective and sustainable distribution.